Impact of SAW RF and IF filter characteristics on UMTS transceiver system performance - Pimingsdorfer, Dieter; Holm, Andreas; Adler, Bernd; Fischerauer, Gerhard; Thomas, Ralf; Springer, Andreas; Weigel, Robert (IEEE Ultrasonics Symposium, 1999)
This paper reports on the application of SAW filters in the Universal Mobile Telecommunications System (UMTS), the new third generation mobile communication system. A brief system overview of the UMTS Terrestrial Radio Access (UTRA) physical layer standardized by the European Telecommunications Standards Institute (ETSI) will be presented. System simulations of a UMTS transceiver designed for commercial use are discussed. SAW filters are applied in both the transmit and receive path of the RF and IF parts. The correlations between filter characteristics, like group delay ripple, effective magnitude and phase errors, and system characteristics, such as Error Vector Magnitude (EVM), are evaluated. Such kind of system simulations covers not only the system design itself but also governs the design of SAW filters since it accounts for the special influence of the SAW RF and IF filter characteristics on the UMTS system performance
elib2cris::1512001600,pimingsdorfer1999